(3VeGfGJ MeGjI GdMbhb hGdMQjGJ GdYGeI (B:s (3OQGSI JMdjdjI ebGQfI (B/s - (3QTjO, eMehO CMeO eMeO Ydjs ((3GdLjRI, eUQ (B:s (3eQcR GdOQGSGJ GdYQHjI,s, 2017)
(3jJfGhd cJGH (B((3VeGfGJ MeGjI GdMbhb hGdMQjGJ GdYGeI (B: (3OQGSI JMdjdjI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3eMehO CMeO eMeO Ydj QTjO(B) (3aj MhGdj (B(487) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdMbhb GdeOfjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdJegjOj (B: (3eaghe GdMbhb hGdMQjGJ GdYGeI hJWhQgG, GdHGH GdChd (B: (3GYJfGb GdOhdI deHOC GdeSGhGI cVeGfI dMeGjI GdMbhb hGdMQjGJ GdYGeI, GdHGH GdKGfj (B: (3GdVeGfGJ GdbGfhfjI dMeGjI GdMbhb hGdMQjGJ GdYGeI(B.s
(3HHdjhLQGajI (B: (3UaMI (B459-482.s
Keywords: (3GdMbhb GdeOfjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdMQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdMQjGJ GdYGeIs; (3GdeSGhGI s; (3SjGOI GdbGfhfs; (3GdSdWI GdbVGFjIs